Progress towards a core set of outcome measures in small-vessel vasculitis. Report from OMERACT 9. - Merkel, P; Herlyn, K; Mahr, A; Neogi, T; Seo, P; Walsh, M; Boers, M; Luqmani, R (2009)
The past decade has seen a substantial increase in the number and quality of clinical trials of new therapies for vasculitis, including randomized, controlled, multicenter trials that have successfully incorporated measures of disease activity and toxicity. However, because current treatment regimens for severe disease effectively induce initial remission and reduce mortality, future trials will focus on any of several goals including: (a) treatment of mild-moderate disease; (b) prevention of chronic damage; (c) reduction in treatment toxicity; or (d) more subtle differences in remission induction or maintenance. Thus, new trials will require outcome measure instruments that are more precise and are better able to detect effective treatments for different disease states and measure chronic manifestations of disease. The OMERACT Vasculitis Working Group comprises international clinical investigators with expertise in vasculitis who, since 2002, have worked collaboratively to advance the refinement of outcome measures in vasculitis, create new measures to address domains of illness not covered by current research approaches, and harmonize outcome assessment in vasculitis. The focus of the OMERACT group to date has been on outcome measures in small-vessel vasculitis with an overall goal of creating a core set of outcome measures for vasculitis, each of which fulfills the OMERACT filter of truth, discrimination, feasibility, and identifying additional domains requiring further research. This process has been informed by several ongoing projects providing data on outcomes of disease activity, disease-related damage, multidimensional health-related quality of life, and patient-reported ratings of the burden of vasculitis.